2021
DOI: 10.3390/healthcare9050577
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Upper Gastrointestinal Examination in Home Care Setting with a Magnetically Assisted Capsule Endoscopy System: A Retrospective Study

Abstract: The magnetic assisted capsule endoscope (MACE) with a hand-held magnetic field navigator (MFN) for upper gastrointestinal examination achieved satisfactory results in a healthy volunteer study. We evaluated the feasibility of upper gastrointestinal examination in the home care setting with the MACE system. Home care patients with upper gastrointestinal symptoms that received an MACE exam were enrolled in the study. MACE procedure time; completeness of observation of important anatomical landmarks; endoscopic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…Several studies have addressed this issue based on different capsule models [ 11 , 12 , 13 , 18 ]; however, no head-to-head or direct comparison study has been conducted for conventional EGD and InsightEyes ® capsule endoscopy system. The completeness of observing upper GI tracts was 93.75% for esophagus, 81.25% for stomach, and 75.00% for the duodenum in a previous small study for a similar population [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have addressed this issue based on different capsule models [ 11 , 12 , 13 , 18 ]; however, no head-to-head or direct comparison study has been conducted for conventional EGD and InsightEyes ® capsule endoscopy system. The completeness of observing upper GI tracts was 93.75% for esophagus, 81.25% for stomach, and 75.00% for the duodenum in a previous small study for a similar population [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Note: Pictures ( g , i ) were adapted from a previously published article with an overlapping study population with permission adapted from Ref. [ 4 ]. 2021, Lin, Y.-C.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…The authors observed that it was possible to capture a greater number of images at specific sites because a greater number of frames were captured per second, and this method facilitated accurate manipulation owing to the traction of the cable. Lin et al [28] performed MCE using this same device in 15 elderly patients with gastric symptoms (dyspepsia, acid reflux, heartburn, epigastric pain, or anorexia). Owing to its portability, out-of-hospital MCE could be performed and home visits were possible.…”
Section: Magnetically Guided Capsule Gastroscopy Using Hand-held Magnetsmentioning
confidence: 99%